Far afield : rare food encounters from around the world - Mitchell, Shane, 1957-; Fisher, James, 1976- (Berkeley : Ten Speed Press, 2016)
James Beard Award-winning journalist Shane Mitchell and photographer James Fisher have traveled the world on assignment for publications such as Travel + Leisure and Saveur. Along the way, they have encountered the fascinating people who are keeping some of the world's oldest food traditions alive: taro farmers in Hawaii who have never left the islands, Maasai warriors in Kenya, and Icelandic shepherds who still use the techniques of their Viking ancestors. Full of compelling photography from far-flung locations, Far Afield profiles these people, sharing their unique and captivating stories along with forty recipes.
Keywords: Mitchell, Shane, -- 1957- -- Travel; International cooking; Travel photography; COOKING / Essays; COOKING / Regional & Ethnic / International; PHOTOGRAPHY / Photoessays & Documentaries; Cookbooks